Proportion of Ugandans with pre-pandemic SARS-CoV-2 cross-reactive CD4+ and CD8+ T-cell responses: A pilot study. - Annemarie Namuniina; Enoch S Muyanja; Victoria M Biribawa; Brenda A Okech; Aloysious Ssemaganda; Matt A Price; Nancy Hills; Ann Nanteza; Bernard Ssentalo Bagaya; Daniela Weiskopf; Catherine Riou; Steven J Reynolds; et al. (Public Library of Science (PLoS), 2023)
The estimated mortality rate of the SARS-CoV-2 pandemic varied greatly around the world. In particular, multiple countries in East, Central, and West Africa had significantly lower rates of COVID-19 related fatalities than many resource-rich nations with significantly earlier wide-spread access to life-saving vaccines. One possible reason for this lower mortality could be the presence of pre-existing cross-reactive immunological responses in these areas of the world. To explore this hypothesis, an exploratory study of stored peripheral blood mononuclear cells (PBMC) from Ugandans collected from 2015-2017 prior to the COVID-19 pandemic (n = 29) and from hospitalized Ugandan COVID-19 patients (n = 3) were examined using flow-cytometry for the presence of pre-existing SARS-CoV-2 cross-reactive CD4+ and CD8+ T-cell populations using four T-cell epitope mega pools. Of pre-pandemic participants, 89.7% (26/29) had either CD4+ or CD8+, or both, SARS-CoV-2 specific T-cell responses. Specifically, CD4+ T-cell reactivity (72.4%) and CD8+ T-cell reactivity (65.5%) were relatively similar, and 13 participants (44.8%) had both types of cross-reactive types of T-cells present. There were no significant differences in response by sex in the population, however this may be in part due to the limited sample size examined. The rates of cross-reactive T-cell populations in this exploratory Ugandan population appears higher than previous estimates from resource-rich countries like the United States (20-50% reactivity). It is unclear what role, if any, this cross-reactivity played in decreasing COVID-19 related mortality in Uganda and other African countries, but does suggest that a better understanding of global pre-existing immunological cross-reactivity could be an informative data of epidemiological intelligence moving forward.